Caenorhabditis elegans as a Model in Studying Physiological Changes Following Heart Failure - Nas, John Sylvester B (Asian Journal of Biological and Life Sciences)
For decades, Caenorhabditis elegans (C. elegans) has been at the forefront of various advances in aging, cancer, and neurodegeneration research. Despite the complete sequencing of this nematode’s genome, there are only a few attempts of using C. elegans in studying the circulatory system and other related physiological activities. The absence of the circulatory system poses a significant challenge for researchers to conduct experiments in this organism. In this paper, the association of the heart and pharyngeal muscle in C. elegans was reviewed to illuminate new understanding and propose potential methods in investigating the physiological changes following pathogen-induced heart failure.
Keywords: Arrhythmia; Caenorhabditis elegans; Heart failure; Infective endocarditis; Pharyngeal muscle